Making the move towards modernized greener separations: introduction of the analytical method greenness score (AMGS) calculator. Issue 7 (14th March 2019) - Hicks, Michael B.; Farrell, William; Aurigemma, Christine; Lehmann, Laurent; Weisel, Lauren; Nadeau, Kelly; Lee, Heewon; Moraff, Carol; Wong, Mengling; Huang, Yun; Ferguson, Paul
Abstract : A single easy-to-use tool to provide a built-in quantitative way to show how method choices impact greenness. Abstract : Green and sustainable processes to develop and manufacture pharmaceuticals using eco-friendly and environmentally responsible means have been underway for over 25 years. These include the major analytical chemistry techniques used for pharmaceutical characterization. The pharmaceutical industry as a whole needs to responsibly transition away from traditional chromatographic methodologies that include the use of longer columns, extended run times, toxic non-polar solvents ( e.g. heptanes and hexanes for normal phase liquid chromatography) and their accompanying large solvent volume consumption - toward more efficient, greener solutions. Over the last decade, high pressure liquid chromatography (HPLC) and supercritical fluid chromatography (SFC) techniques have undergone substantial improvements to instrumentation ( e.g. UHPLC and UHPSFC) and column particle technologies, all of which lead to faster and more efficient separations while reducing development and validation time for both chiral and achiral analyses. However, many of these advances have yet to be globally adopted in later stage drug development and manufacturing where chromatographic process usage requires multiple analyses for every method transfer, validation, and clinical supply campaign. In order to emphasize greener method alternatives, we introduce a new approach to definitively establish the impact of method design and instrument selection choices. Our aim is to provide awareness and guidance to the global industry with a single unified, straightforward metric that clearly shows the benefit of selecting more modernized, safer and more environmentally-friendly methods and techniques without compromising separation performance.